Effect of Fish Fortified Amaranthus Cruentus and Solanum Macrocarpon Powder on Anaemia and Vitamin A Status of 4 to 8 – Year – Old School Children in Kodzobi, Adaklu District of Ghana. - Tohouenou, M.M. (University Of Ghana, 2019)
Background: Anaemia, vitamin A deficiency and infections are widespread among Ghanaian children of school-going age and are topics of public health concern. Several interventions including supplementation have been implemented over the years to improve the situation, however the problem persists. Globally, food-based approaches have been recognized as more sustainable in addressing micronutrient deficiencies. In Ghana there is a lack of knowledge on using a combination of fish and vegetables powder as a food-based intervention in combating anaemia and vitamin A deficiency. Objective: The research sought to investigate the effect of consumption of fish fortified Amaranthus cruentus and Solanum macrocarpon powder on anaemia and vitamin A status of 4 to 8-year old school children at Kodzobi in Adaklu District of the Volta Region of Ghana. Methods: The study was a randomized controlled trial with data collection point at baseline and end line and a four-month nutrition intervention period. Three groups made up of 54 children each were identified to participate in the study through random sampling. Parental and participant background information was collected using questionnaires. Haemoglobin and serum retinol concentrations were determined using the heamocue haemoglobinometer and the high-performance liquid chromatography respectively. The Giemsa staining and the Kato-Katz techniques were employed to examine malaria-parasitaemia and soil-transmitted helminths infections respectively. Dietary data were collected using the 24-hour recall method and a food frequency questionnaire. Using WHO standard procedures, weight and height measurements were taken to assess participants‟ anthropometric nutritional status. Haematological indices and dietary data were normally distributed so means ± standard deviations were used to present their summary values. Outcome measures of variables (haemoglobin, serum retinol, dietary nutrient intakes, Z - scores) were compared within groups using paired T-test for continuous variables and chi-square for categorical variables. Analysis of co-variance (ANCOVA) was used to test for differences in mean changes among the 3 groups and between paired groups to determine any significant differences. Binary logistic regression was used to determine factors associated with anaemia and vitamin A deficiency whilst adjusting for potential confounders. Results: At baseline, the mean haemoglobin concentration of the two intervention groups A and B and the control group C were 12.0 ± 1.1 g/dl, 11.4 ± 1.0 g/dl and 11.6 ± 1.0 g/dl respectively. At end line, it was 12.4 ± 1.3 g/dl, 11.8 ±1.9 g/dl and 11.6 ± 1.3 g/dl for groups A, B and C respectively. A significant difference in mean haemoglobin concentration was recorded across the groups at p = 0.024 at post-intervention. At baseline, the prevalence of anaemia was 46.3 %, 51.9 % and 42.9 % for groups A, B and C respectively. At the end of the intervention period, the prevalence of anaemia reduced to 34.5 %, 45.2 % 41.2 % for intervention groups A, B and the control group C respectively. The difference in the prevalence of anaemia across the groups was significant at p = 0.036. The mean serum retinol concentrations of the three groups (A, B and C) at baseline were 23.1 ± 7.3 μg/dl, 22.3 ± 5.6 μg/dl and 22.8 ± 6.8 μg/dl respectively. At end line, it increased to 28.3 ± 8.8 μg/dl, 24.7 ± 6.5 μg/dl and 23.8 ± 6.5 μg/dl for groups A, B and C. A significant difference in serum retinol concentration was recorded across the groups at p = 0.044. Prevalence of vitamin A deficiency decreased from 31.5 % to 9.6 % for intervention group A; 29.6 % to 20.0 % for intervention group B and 35.2 % to 29.4 % for the control group C from baseline to end line respectively. Across the groups, differences in vitamin A deficiency (VAD) at the beginning and end of the study were not significant. Malaria was prevalent among the participants at the baseline and at the end of the study. Malaria prevalence declined from baseline to end line within the three groups: group A 46.3 % to 13.5 %; group B 25.9 % to 10.0 % and group C from 38.9 % to 9.8 %, however, the decreases were not statistically significant. Only one participant was reported to have hookworm infestation. Serum retinol level was significantly associated with anaemia. Marital status and anaemia status were the factors significantly associated with vitamin A deficiency. Conclusion: Anaemia and vitamin A deficiency are problems of public health significance in school-aged children in Kodzobi at Adaklu District. Fish fortified Amaranthus cruentus and Solanum macrocarpon powder improved the haemoglobin concentration of participants significantly and so has the potential to reduce anaemia prevalence but not vitamin A status of the study participants.
PhD. Nutrition Science
Keywords: Fish; Amaranthus Cruentus; Solanum Macrocarpon; Anaemia; Adaklu District